Algorithms and models for the web-graph : 6th international workshop, WAW 2009, Barcelona, Spain, February 12-13, 2009 : proceedings - Avrachenkov, Konstantin (Springer, 2017)
This book constitutes the refereed proceedings of the 6th International Workshop on Algorithms and Models for the Web-Graph, WAW 2009, held in Barcelona, Spain, in February 2009 - co-located with WSDM 2009, the Second ACM International Conference on Web Search and Data Mining. The 14 revised full papers presented were carefully reviewed and selected from numerous submissions for inclusion in the book. The papers address a wide variety of topics related to the study of the Web-graph such as theoretical and empirical analysis of the Web graph and Web 2.0 graphs, random walks on the Web and Web 2.0 graphs and their applications, and design and performance evaluation of the algorithms for social networks. The workshop papers have been naturally clustered in three topical sections on graph models for complex networks, pagerank and Web graph, and social networks and search.